Analysis of Community Understanding of E-Commerce-Based Information Systems in Klambir V Village Kebun Deli Serdang - Noviani; Nur Aliah; Samrin (International Journal of Management, Economic and Accounting, 2023)
The economy of Klambir V Kebun Village, Kec Hamparan Perak, Deli Serdang Regency, is starting to develop due to the availability of village funds from the central government and support from information technology such as the Internet which aims to improve the local economy. Information technology provides various solutions to the problems that are generally faced by people in developing their businesses. For example, one of the technologies that is currently developing rapidly is Electronic Commerce (E-Commerce). E-Commerce itself is interpreted by some experts as financial buying and selling transactions that use an internet connection or digital technology. Various transactions, from sales, purchases, distribution, to marketing of goods and services can be done by utilizing E-Commerce. However, the author sees that many people in Klambir V Kebun Village, Deli Serdang Regency, still do not know the benefits and how to use E-Commerce. Based on this phenomenon, the author is interested in developing an E-Commerce-based information system with the aim of improving the economy and service to the people of Klambir V Kebun Village.